Toward detailed modeling of tires with linear elastic rubber compounds using finite element method - Sadjiep Tchuigwa, Baurice Sylvain; Krmela, Jan; Pokorný, Jan (IOP Publishing LTD, 2024)
Against a backdrop of increasing depletion of natural and energy resources and worsening global warming, the tire industry, like many other industries, is currently confronted with the pressing need to enhance not only its resilience but also the sustainability and cost-effectiveness of its products through advanced numerical simulations. Numerical simulation is a valuable tool in the tire development process that provides manufacturers with in-depth insights into their products from design to mass production. This paper aims to introduce a detailed finite element-based modeling process for tires that can be used for a wide range of simulations, including steady state, transient rolling, and failure scenarios such as layer delamination, blowout, and part breakage. The selected tire for the implementation in this study is designated 175/75R14 and was modeled in a static loading setup in ABAQUS standard with an implicit scheme considering linear elastic rubber compounds and other assumptions. Unlike the commonly used homogenized approach for reinforced layers, the proposed method takes into account the real physical and mechanical properties of the tire structure. In addition, important information pertaining to the creation of mesh and the interactions between elements is provided. The obtained results align with the assumptions and can serve as a proof of concept for more detailed and advanced tire modeling and enhancement in the future.
K detailnímu modelování pneumatik s lineárně elastickými elastomerovými směsmi metodou konečných prvků
Keywords: tire; rubber; FEM; pneumatika; elastomer; MKP